Kewenangan Jaksa Pengacara Negara Mewakili BUMN Sebagai Pihak Termohon Dalam Suatu Permohonan Kepailitan Dan PKPU - Muhammad Akram Rafii Latuconsina; Elisatris Gultom; Aam Suryamah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
State-Owned Enterprises (BUMN) are one of the actors in economic activities in the national economy which have an important role in realizing the welfare and prosperity of society. In the case of bankruptcy and postponement of debt payment obligations applications, the Prosecutor's Office has the authority to file a bankruptcy application against the debtor on the basis of public interest. On the other hand, the Prosecutor's Office can also act as a state attorney who has the authority to represent the state or state agency in a case. From the research results, it can be concluded that the authority of the State Attorney to represent the state/state agencies in commercial cases is different from civil cases in general as regulated by Law No. 37 of 2004 concerning Bankruptcy and postponement of debt payment obligations.